The names of reality. Autofiction in Formas de volver a casa [Ways of Going Home] - Saavedra Galindo, Alexandra (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This work focuses on the study of the novel Formas de volver a casa [Ways of going home] (2011), by the Chilean writer Alejandro Zambra, with particular attention to the analysis and description of the auto-fictional procedures used. The reading of the novel attends to subjects such as memory, the past, childhood remembrances, the author’s self-exposure through fictional procedures, as well as to the name games and puzzles that determine the relationships between different characters and the author. The facts that determine the time frame of the work -two earthquakes in Chile (1985 and 2010) and the period of Augusto Pinochet’s dictatorship- are also considered